Enhancing elementary school teachers’ understanding and practical skills in implementing a deep learning approach - Hartono Hartono; Kurniawan Yudhi Nugroho; Choiril Anwar; Mega Mulianing Maharani; Sugeng Hariyadi (LPPM Universitas Islam Sultan Agung, 2026)
Since early 2025, the Indonesian government, c.q. The Ministry of Primary and Secondary Education has introduced a deep-learning approach to primary and secondary education. This new approach aims to improve education quality by relying on three pillars: mindful, meaningful, and joyful learning. Many elementary school teachers, however, have not fully understood the approach due to limited access to training and professional development programs. Considering this, the community service team from the English Education Study Program at Sultan Agung Islamic University held a one-day workshop to help enhance elementary school teachers' understanding and ability to apply the approach in their classrooms. The workshop was a collaboration between the community service team and the Ahmad Yani Teacher Working Group (KKG), and was held on November 27, 2025, at the SDN Bergas Lor 01, Bergas subdistrict, Semarang Regency. Fifty-five teachers from various elementary schools in the KKG area participated in the workshop. They were presented with the deep learning approach and related topics, such as growth mindset, assessment in deep learning, the SOLO taxonomy, teaching strategies, and more. They worked in groups, discussed, and demonstrated learning strategies. After the workshop, participants were given assignments to deepen the material. Feedback from the survey suggests that the teachers participated well and enjoyed the workshop, finding it beneficial for developing their skills. However, due to time constraints, the workshop was unable to fully explore the deep learning approach. Therefore, more training and workshops are still needed.